Who governs now? The politics of power in the applied sciences NYC initiative - Bright, J (2019)
This thesis explores the politics of power in the policy decision-making processes of Applied Sciences NYC, an economic development initiative under the administration of Mayor Michael Bloomberg (2002–2013) in New York City. I seek to understand the politics of power in policy decision-making processes of both data-driven governance and public participation. The literature on the politics of power in public policy decision-making processes does not adequately address public policy decision-making processes of both public participation and data-driven governance. What power dynamics explain the policy decision-making processes in Applied Sciences NYC? And, given the norm of data-driven policy decision-making under the Bloomberg administration and the Applied Sciences NYC power dynamic, why also include public participation in the policy decision-making processes of Applied Sciences NYC? New York City governmental officials intimated and publically professed that a multiplicity of non-governmental actors possessed power in the policy decision-making processes of Applied Sciences NYC. Via process-tracing methodology, I provide nuance to this suggestion of pluralist power. I observe that mayoral agency—and in particular the mayor’s definition of economic development, his norm of data-driven policy decision-making, and his personal background—played a decisive role in the policy decision-making processes of Applied Sciences NYC. In so doing, mayoral agency closed the policy decision-making processes of Applied Sciences NYC such that only certain ideas were considered and only certain participants were included. I maintain that New York City governmental officials nonetheless included processes of public participation in Applied Sciences NYC with three primary goals: to generate ideas and validate their hypotheses; to mitigate future criticism; and to catalyze support. These research findings may inform conversations on public trust, openness, and inclusivity in American democracy. Further empirical work is necessary to understand if my findings with regard to power dynamics in the policy decision-making processes of Applied Sciences NYC also apply to other cases.